Elevated urinary phthalate levels in endometrial cancer patients: Evidence from a comparative study - Hao Lin; Wen-Chin Lee; Yin-Yi Chen; Fu-Jen Cheng; Wan-Ting Huang; Kai-Fan Tsai; Shau-Hsuan Li; Chia-Te Kung; Yu-Che Ou (Ecotoxicology and Environmental Safety)
Phthalates are common plasticizers with endocrine-disrupting properties. Although laboratory studies suggest links to estrogen-dependent cancers, their association with endometrial cancer (EC) in humans remains unclear. This study investigated urinary phthalate metabolite levels in relation to EC and explored potential lifestyle and dietary contributors to phthalate exposure. A total of 232 women, including 116 EC patients and 116 healthy controls, were enrolled. Urine samples were analyzed by UPLC-MS/MS to measure eight phthalate metabolites, adjusted for creatinine. Lifestyle and dietary information were collected via questionnaires. Logistic regression assessed associations between phthalate levels and EC, while Spearman’s correlation examined inter-metabolite relationships. All eight metabolites were detected in over 90 % of participants, with significantly higher concentrations in the EC group. Among them, mono-benzyl phthalate (MBzP) was the only metabolite independently associated with EC (OR 3.712, 95 % CI 1.464–9.414, p = 0.006). Using a cutoff value of 0.145 µg/g Cr, EC remained the only independent predictor of elevated MBzP levels (OR 5.696, 95 % CI 2.572–12.615, p < 0.001). No significant associations were found between MBzP levels and lifestyle or dietary habits. Correlations among phthalate metabolites were generally consistent across groups, though MBzP showed weaker correlations, indicating potentially distinct exposure pathways. This study is the first to demonstrate an independent link between urinary MBzP levels and EC in humans. The lack of lifestyle or dietary influence highlights the complexity of exposure sources, emphasizing the need for further research to understand underlying mechanisms and environmental factors contributing to phthalate exposure.